A secret language of aggression: disgust expressions are treated as cues of impending social exclusion among women - Krems, Jaimie Arona; French, Juliana; Filip-Crawford, Gabrielle (Frontiers in Social Psychology, 2024)
Attending to women's intrasexual competition generates a straightforward prediction: Insofar as women actors sometimes use distinct tactics of aggression (e. g., related to social exclusion), women targets might possess distinct interpretations of and reactions to those tactics. We test this using one such tactic common among women: disgust expressions directed at targets of desired social exclusion. Across four experiments with U.S. adults (N = 1,019), women (more than men) (1) interpret same-gender disgust (but not anger) facial expressions potentially directed toward them as cues of impending social exclusion, and (2) report being hurt in reaction to these expressions, whether imagined or recalled. Further, (3) women (but not men) who are more dispositionally concerned with social belonging (but not vulnerability to disease) report greater hurt. Women seem to possess distinct interpretations of and reactions to aggression tactics that they uniquely and recurrently face. Identifying these often lesser-studied challenges women face may reveal additional, overlooked features of women's strategic social cognition and behavior.